Design a solar clean car - Mahfuz, Md. Muntashir Bin; Md. Tahsin-ul-Islam (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.